Distinct B subunits of PP2A regulate the NF‐κB signalling pathway through dephosphorylation of IKKβ, IκBα and RelA. Issue 24 (3rd December 2017) - Tsuchiya, Yoshihiro; Osaki, Keiko; Kanamoto, Mayu; Nakao, Yuki; Takahashi, Ena; Higuchi, Toru; Kamata, Hideaki
Abstract : PP2A is composed of a scaffolding subunit (A), a catalytic subunit (C) and a regulatory subunit (B) that is classified into four families including B, B′, B′′ and B′′′/striatin. Here, we found that a distinct PP2A complex regulates NF‐κB signalling by dephosphorylation of IKKβ, IκBα and RelA/p65. The PP2A core enzyme AC dimer and the holoenzyme AB′′′C trimer dephosphorylate IKKβ, IκBα and RelA, whereas the ABC trimer dephosphorylates IκBα but not IKKβ and RelA in cells. In contrast, AB′C and AB′′C trimers have little effect on dephosphorylation of these signalling proteins. These results suggest that different forms of PP2A regulate NF‐κB pathway signalling through multiple steps each in a different manner, thereby finely tuning NF‐κB‐ and IKKβ‐mediated cellular responses. Abstract :